The role of propulsive force deterioration in the deceleration phase of elite sprinting - Connick, M. J. (Journal of Science and Medicine in Sport, 2025)
Objectives The deceleration phase of sprinting is important to pacing as it is associated with reduced capacity to produce propulsive force. This study aimed to quantify the propulsive force deterioration (PFD) rate and its relationships with deceleration rate, maximum velocity (vmax), and finishing velocity (vfinish) in 100m, 200m, and 400m elite-level sprinters. Specifically, it aimed to quantify how differences in event-specific demands influence these relationships.